Kinetic and Kinematic Analyses of Countermovement Jump in a Small Sample of Individuals with Congenital Vision Loss. Issue 3 (June 2022) - Iguchi, Masaki; Nozu, Shojiro; Sakuma, Toru
In the present study, we aimed to explore whether countermovement jumps (CMJs) performed by young adults with and without visual impairment (VI) differ. We compared three participants with congenital VI to 10 participants without congenital VI when both groups performed CMJs with maximum effort. Although the maximum jump height did not differ between groups, all three participants with VI showed such reduced maximum downward velocity of the center of body mass and a relative net negative vertical impulse that, on these measures, they fell beyond two standard deviations from the mean scores of participants without VI. The range of motion for the leg joints and countermovement depth did not differ between groups. Although findings from our small sample should be cross-validated and trainers should take care to protect athletes from falls, it appears from our preliminary data that a path to improved CMJ performance for athletes with VI is to increase their movement velocity in the countermovement phase of the jump.